Unpacking Power and Identity: The Theoretical Foundations and Methodological Commitments of Gender Critique - Amatya, Naresh (Journal of Nepalese Studies, 2025)
This article critically examines the theoretical foundations and methodological commitments of gender critique as an interdisciplinary framework for analyzing gendered power relations. Drawing on feminist, queer, postcolonial and poststructuralist theories, it explores how gender is performatively constructed and institutionally enforced through sociocultural mechanisms. Emphasizing anti-essentialism, intersectionality and decolonial epistemologies, the study outlines the core theoretical concepts underlying gender critique and demonstrates their relevance in analyzing contemporary gender issues. It also engages with challenges from biological determinism, materialist feminism and western-centric frameworks, arguing for a reflexive and context-sensitive approach to knowledge production. Methodologically, the article underscores the significance of qualitative, reflexive, participatory and discourse-based research practices that center marginalized voices and challenge epistemic hierarchies. The article also discusses the relevance of feminist standpoint theory, critical discourse analysis and decolonial methods in contemporary gender research. By interweaving theory and praxis, gender critique emerges as a dynamic and politically engaged field that addresses urgent global issues such as trans rights, algorithmic bias and environmental injustice. Ultimately, it argues that gender critique must remain adaptable, inclusive and politically engaged, fostering new vocabularies of resistance and envisioning equitable futures across social, cultural and technological domains.